TAMI-42. H3K27M MUTANT GLIOMAS HIJACK A CONSERVED AND CRITICAL METABOLIC PATHWAY USED BY IDH1 MUTANT GLIOMAS TO MAINTAIN THEIR PREFERRED EPIGENETIC STATE - Chung, Chan (Neuro Oncol, 2020)
H3K27M-midline gliomas are fatal tumors that mainly harbor H3.3K27M mutations resulting in global H3K27me3 reduction that impacts neuroglial-differentiation. However, the exact mechanisms by which H3.3K27M mutations promote cancer are poorly understood. Metabolic reprogramming is a hallmark of cancer and we hypothesized that H3.3K27M mutations can reprogram metabolism to support uncontrolled growth. We demonstrate that H3.3K27M-mutant cells show elevated levels of critical enzymes related to glycolysis and TCA cycle metabolism including hexokinase-2, isocitrate dehydrogenase (IDH)-1 and glutamate dehydrogenase. H3.3K27M cells also demonstrated enhanced glycolysis, glutamine and TCA-cycle metabolism accompanied by increased alpha-ketoglutarate (α-KG) production. Mutant IDH (mIDH)1/2 converts α-KG to D-2-hydroxyglutarate (D-2HG). D-2HG increases H3K27me3 by inhibiting α-KG’s function to drive H3K27-demethylases. We discovered that H3.3K27M cells use α-KG in an opposing manner to maintain low H3K27me3. Inhibiting enzymes related to α-KG generation including hexokinase-2, glutamate-dehydrogenase and wild type-IDH1 increased global H3K27me3, altered chromatin accessibility at neuroglial-differentiation factors and lowered tumor cell proliferation. In vivo inhibition of glutamine metabolism and/ or wild type-IDH1 using blood-brain barrier penetrant small molecule inhibitors increased overall survival in vivo in two independent H3.3K27M animal models (p< 0.0001). H3K27M and mIDH1 were mutually exclusive in patient tumor samples and D-2HG treatment or forced-mIDH1 expression in H3.3K27M cells increased global H3K27me3 and cell death. Finally H3.3K27M and mIDH1 were synthetic lethal in vitro. Our data suggest that H3.3K27M and mIDH1 hijack a critical and conserved metabolic pathway in opposing manners to regulate global H3K27me3. These results have implications for understanding the pathogenesis of fatal H3K27M-gliomas and for developing therapeutic strategies by disruption of an integrated metabolic/epigenetic-axis.